(untitled) (Fiep Bulletin - online, 2014)
By means of case studies at children with Down syndrome we have introduced some knowledge about practical training of swimming and have described differences in didactics of swimming of disabled and healthy children. We used an action research at case studies method. Disabled children (2 boys, age 11, 12) were an experimental group. Healthy pupils (n=14, age 8-9) were a comparison group. The course of disabled children lasted 1 year. The course of healthy children lasted 6 months twice a week. Control tests at the end of the course included 25 m crawl and backstroke legs swimming with noodles, breathing into water while swimming with a swimming board. Differences in didactics for experimental group: exercises only with direct help from the teacher in water, lower variability of exercises within an exercise unit, simple form of imitation of swimming motion out of water, limited cognitive part of exercises. Pupils in the experimental group accomplished the control test in limited extent. After one year of swimming course they were able to swim 25 m backstroke legs, 25 m crawl legs but not able to breath into water while swimming 25 m with a swimming board. These units require longer training. The comparison group successfully managed all the motoric tests.